Facile synthesis, spectral characterization, antimicrobial and in vitro cytotoxicity of novel N3,N5-diisonicotinyl-2,6-dimethyl-4-phenyl-1,4-dihydropyridine-3,5-dicarbohydrazide derivatives - Karthikeyan Elumalai; Manogaran Elumalai; Kalpana Eluri; Sivaneswari Srinivasan; Mohamed Ashraf Ali; Basu Venkateswara Reddy; Sarada Prasad Sarangi (Faculty of Pharmacy, Cairo University, 2016)
A new series of some novel isoniazid condensed 1,4-dihydropyridines was prepared by reaction of N-(3-oxobutanoyl) isonicotinohydrazide with aryl aldehyde and 25-30% ammonia solution in the presence of catalytic amount of barium nitrate as an efficient catalyst. The confirmation of the chemical structure of the synthesized compounds (4a-m) was substantiated by TLC, different spectral data IR, 1H NMR, 13C NMR, and mass spectra and elemental analysis was done. The synthesized compounds were evaluated for antimicrobial activity and cytotoxicity against Gram-positive bacteria Bacillus subtilis, Gram-negative bacteria Escherichia coli and Vero cells. All the reported compounds exhibited weak, moderate, or high antimicrobial activity and cytotoxicity. Especially, compound 4i showed the best antimicrobial activity and cytotoxicity of all the 1,4-dihydropyridine derivatives, with an MIC value of 11.5 μM, 12.2 μM and a CTC50 value of 27 μM.